Brentuximab vedotin in combination with lenalidomide and rituximab in subjects with relapsed or refractory diffuse large B-cell lymphoma (DLBCL) (Trials in Progress) - Bartlett, Nancy L.; Yasenchak, Christopher A.; Ashraf, Khaleel K.; Harwin, William N.; Sims, Robert Brownell; Nowakowski, Grzegorz S. (Journal of clinical oncology, 2021)
TPS7571Background: The majority of patients (pts) with relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL) who relapse after HSCT, or who are not candidates for HSCT have poor outcomes and are in need of novel therapies. Brentuximab vedotin (BV) is a CD30-directed ADC and preclinical data provide a strong rationale for combining BV, lenalidomide, and rituximab in the treatment of R/R DLBCL. In addition, in a phase 1 trial in which 37 pts with R/R DLBCL were treated with BV + lenalidomide, the ORR was 56.7% (73.3% in CD30+ pts; manuscript in preparation). The median duration of remission was 13.2 months in pts with a CR or PR and 11.7 months in pts with CR, PR, or stable disease > 6 months. The PFS and median OS were 11.2 months and 14.3 months, respectively and results were similar in the CD30+ and CD30 < 1% groups. The clinical activity and manageable safety profiles of BV, lenalidomide, and rituximab as single agents, make the combination a viable option in multiply relapsed and heavily pretreated pts. Methods: This is a randomized, double-blind, placebo-controlled, active-comparator, multicenter phase 3 study designed to evaluate the efficacy of BV vs placebo, in combination with lenalidomide + rituximab, in subjects with R/R DLBCL (NCT04404283). Prior to randomization, there will be a safety and PK run-in period where 6 pts will receive BV, lenalidomide + rituximab, and safety and PK will be evaluated after the first cycle of treatment; 6/6 subjects have been enrolled. Key eligibility criteria include: pts aged ≥18 with R/R DLBCL with an eligible subtype; ≥2 prior lines of therapy and must be ineligible for, or have declined, stem cell transplant, and chimeric antigen receptor T-cell (CAR-T) therapy; ECOG 0 to 2; fluorodeoxyglucose-avid disease by PET and bidimensional measurable disease of at least 1.5 cm by CT. Patients (n = 400) will be randomized 1:1 to receive either BV or placebo in combination with lenalidomide + rituximab and will be stratified by CD30 expression (positive [ ≥1%] versus < 1%), prior allogeneic or autologous stem cell transplant therapy (received or not), prior CAR-T therapy (received or not), and cell of origin (GCB or non-GCB). The primary endpoints are PFS per BICR in the ITT and CD30+ populations. Key secondary endpoints are OS in the ITT and CD30+ populations, and ORR per BICR. Other secondary endpoints include CR rate, duration of response, and safety and tolerability of the combination. Disease response will be assessed by BICR and the investigator according to the Lugano Classification Revised Staging System. Radiographic disease evaluations, including contrast-enhanced CT scans and PET, will be assessed at baseline, then every 6 weeks from randomization until Week 48, then every 12 weeks. PET is not required after CR is achieved. The trial is currently enrolling and will be open in 16 countries. Clinical trial information: NCT04404283.